Gelitten, gestorben, auferstanden: Passions- und Ostertraditionen im antiken Christentum ; [zwei Tagungen: ein Seminar ... auf der Jahrestagung der Society of Biblical Literature in San Diego, Kalifornien im November 2007 und ein Treffen ... auf der "International Conference on Patristic Studies" im August 2007 in Oxford] - Nicklas, Tobias (Wissenschaftliche Untersuchungen zum Neuen Testament, 2010)
Cover; Vorwort; Inhaltsverzeichnis; ISTVÁN CZACHESZ: Passion and Martyrdom Traditions in the Apocryphal Acts of the Apostles; 1. The transmission of stories: a cognitive psychological model; 2. Passion and Martyrdom: Common Origins?; 3. The Death of the Martyr; 4. Conclusion; DEREK S. DODSON: Dream Magic: The Dream of Pilate's Wife and the Accusation of Magic in the Acts of Pilate; 1. The Accusation of Magic; 2. The Accusation in Context of Ancient Dream Magic; 3. Reading Acts of Pilate 2.1 in Light of Ancient Dream Magic; 4. Conclusion